Analysis of the Impact of Place and Promotional Strategies of Marketing Mix towards Consumer Purchase Decision in Marutama Ramen - Jocelyn, Jocelyn; Amelia, Amelia (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
In the world where business has been rapidly growing over the time, the competition among the businesses has been tremendously increasing day by day. Where competition has been fierce, companies will have to think on ways to maximize their sales and also on how to develop the best and most effective strategies to market their products. Companies are to ensure that they implement and take on the best decision for their own in order to push the customer purchase decision. This study aims to analyze the impact of Place and Promotional Strategies of Marketing Mic towards Consumer Purchase Decision in Marutama Ramen Medan. The sample used in this study is 100 respondents. For processing and analyzing data in this study, namely by using SPSS version 25.0 as software for data processing. This study has 2 hypotheses and all of them have significant results.Place Strategy, Promotion Strategy, Customer Purchase Decision